Fundamentals of aerospace navigation and guidance - Kabamba, Pierre T.; Girard, Anouck (Cambridge : Cambridge University Press, 2014)
This text covers fundamentals used in the navigation and guidance of modern aerospace vehicles, in both atmospheric and space flight. It can be used as a textbook supporting a graduate level course on aerospace navigation and guidance, a guide for self-study, or a resource for practicing engineers and researchers. It begins with an introduction that discusses why navigation and guidance ought to be considered together and delineates the class of systems of interest in navigation and guidance. The book then presents the necessary fundamentals in deterministic and stochastic systems theory and applies them to navigation. Next, the book treats optimization and optimal control for application in optimal guidance. In the final chapter, the book introduces problems where two competing controls exercise authority over a system, leading to differential games. Fundamentals of Aerospace Navigation and Guidance features examples illustrating concepts and homework problems at the end of all chapters.
Machine generated contents note: 1. Introduction; 2. Deterministic systems theory; 3. Stochastic systems theory; 4. Navigation; 5. Homing guidance; 6. Ballistic guidance; 7. Midcourse guidance; 8. Optimization; 9. Optimal guidance; 10. Introduction to differential games; Epilogue; A. Useful definitions and mathematical results; A.1. Results from topology; A.2. Results from linear algebra; A.3. Taylor's theorem; A.4. Newton's method; A.5. The implicit function theorem.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Navigation (Astronautics); Space vehicles; Trajectory optimization; Space flight